Siedlungsentwicklung und Bevölkerungsdynamik an der Peripherie der chilenischen Metropole Groß-Santiago.: Das Beispiel des Stadtteils La Granja - Bähr, Jürgen (ERDKUNDE, 1976)
The regular modification of population density with increasing distance from the town centre in the period 1940-1970 has been examined in the case of Santiago de Chile. It would appear that, starting in the 'fifties/ such a change took place which transformed the compact colonial town into an overflowing agglomeration (decreasing density gradient and decreasing central density). A thorough analysis of the connection between migration and peripheral growth in the comuna La Granja permitted identification of some events and forces which caused this development process. It was possible to prove that the different physiognomy of three more closely observed residential areas coincides with a differing age and domestic structure, and, therefore, that its formation and metamorphosis runs parallel with certain phases of external or internal migration movements of the town. The migration cycle begins with the movement of single, and at that stage externally-resident persons, into the metropolis of Santiago. The young immigrants concentrate partly on derelict, centrally-situated lodgings (predominantly men) and in non-marginal residential quarters (especially women as domestic servants). On the other hand they first try to find accommodation with friends or relatives already settled in Santiago, or to rent a room with their help (i.e. with these people acting as agents). The move to the shanty towns on the periphery of the town only occurs at a later stage in life, and is linked with marriage and the birth of children. In the course of years these makeshift hut settlements develop into somewhat better equipped mejoras, which are also still built on a self-help basis, or into poblaciones with simple and monotonously arranged, mainly single-storeyed terrace houses, erected by the state building societies. Together with the consolidation process the inhabitants of these settlements see their possibilities opening up if they can offer their homes at least temporary accommodation to friends. Thus a new migration cycle begins.